Intrinsic and Synaptic Properties Shaping Diverse Behaviors of Neural Dynamics - An, Lingling; Tang, Yuanhong; Wang, Doudou; Jia, Shanshan; Pei, Qingqi; Wang, Quan; Yu, Zhaofei; Liu, Jian K. (Frontiers in Computational Neuroscience, 2020)
The majority of neurons in the neuronal systems of the brain have a complex structure of the morphology, which diversifies the dynamics of neurons. In the granule layer of the cerebellum, there exists a unique cell type, unipolar brush cell (UBC), serving as an important relay cell to transfer information from outside mossy fibers to downstream granule cells. The distinguishing feature of UBC is that it has a simple morphology with only one short dendritic brush connected its soma. Based on experimental evidence showing that UBCs exhibit a variety of dynamic behaviors, here we develop two simple models, one with a few detailed ion channels for simulation, and the other one as a two-variable dynamical system for theoretical analysis, to characterize the intrinsic dynamics of UBCs. The reasonable values of the key channel parameters of the models can be determined by analysis of the stability of the resting membrane potential and the rebound firing properties of UBCs. Together with a large variety of synaptic dynamics installed on UBCs, we show the simple structured UBCs, as relay cells, can extend the range of dynamics and information from input mossy fibers to granular cells with low-frequency resonance, and transfer the stereotyped input to diverse amplitudes and phases of the output for downstream granule cells. These results suggest that neuronal computation, embedded with intrinsic ion channels and diverse synaptic properties on single neurons without sophisticated morphology, can shape a large variety of dynamic behaviors to enhance the computational ability of local neuronal circuits.